World of CrayfishTM: a web platform towards real-time global mapping of freshwater crayfish and their pathogens - Ion, Mihaela C.; Bloomer, Caitlin C.; Barascu, Tudor I.; Oficialdegui, Francisco J.; Shoobs, Nathaniel F.; Williams, Bronwyn W.; Parvulescu, Lucian (Peerj Inc, 2024)
Freshwater crayfish are amongst the largest macroinvertebrates and play a keystone role in the ecosystems they occupy. Understanding the global distribution of these animals is often hindered due to a paucity of distributional data. Additionally, nonnative crayfish introductions are becoming more frequent, which can cause severe environmental and economic impacts. Management decisions related to crayfish and their habitats require accurate, up-to-date distribution data and mapping tools. Such data are currently patchily distributed with limited accessibility and are rarely up-todate. To address these challenges, we developed a versatile e-portal to host distributional data of freshwater crayfish and their pathogens (using Aphanomyces astaci, the causative agent of the crayfish plague, as the most prominent example). Populated with expert data and operating in near real-time, World of CrayfishTM is a living, publicly available database providing worldwide distributional data sourced by experts in the field. The database offers open access to the data through specialized standard geospatial services (Web Map Service, Web Feature Service) enabling users to view, embed, and download customizable outputs for various applications. The platform is designed to support technical enhancements in the future, with the potential to eventually incorporate various additional features. This tool serves as a step forward towards a modern era of conservation planning and management of freshwater biodiversity.
Keywords: Aphanomyces astaci; Endangered species; Invasive species; Open data; Astacidae; Cambaridae; Species distribution; Parastacidae